Gendered workplaces: Resistance, adaptation and agency in large legal firms: The perspectives of young lawyers - Santos, S. (Portuguese Journal of Social Science, 2020)
Gender inequality at work is a persistent and complex phenomenon. Taking the case of a small group of young lawyers working in large legal firms in Portugal, this article intends to discuss how gender inequality manifests and evolves from internship through first years of professional activity. Based on a data set of nineteen biographical interviews – ten male and nine female – we discuss the centrality of gender in analysing professional organizations, combining structural and actor perspectives. Female and male lawyers are confronted with a gendered organization with (in)visible gender lines that naturalize asymmetries of treatment, position, opportunities and expectations. Both learn how to adapt and invent strategies of resistance that include flexible professional projects.